2007
DOI: 10.1016/j.breast.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of non-informative HER-2 immunoreactions (2+) in breast carcinomas with FISH, CISH and QRT-PCR

Abstract: The routine assessment of HER-2 expression can be affected by many immunohistological preanalytical and analytical variables. The evaluation of non-informative HER-2 tests, because of 2(+) scores, has been addressed in studies using in situ hybridization (fluorescent in situ hybridization (FISH) or chromogenic in situ hybridization (CISH)). There are very few studies that additionally checked 2(+) cases by quantitative reverse transcription-PCR (QRT-PCR). We analyzed totally 195 breast carcinoma cases, 70 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 69 publications
5
21
0
Order By: Relevance
“…We observed high agreement between qRT-PCR and FISH, similar to some other studies (Kostopoulou et al, 2007;Baehner et al, 2010). The qRT-PCR method was positive by both FISH and MLPA, while one sample with overexpression detected by qRT-PCR had negative results in the other two tests (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…We observed high agreement between qRT-PCR and FISH, similar to some other studies (Kostopoulou et al, 2007;Baehner et al, 2010). The qRT-PCR method was positive by both FISH and MLPA, while one sample with overexpression detected by qRT-PCR had negative results in the other two tests (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…Kostopoulou et al [7] also confirmed that mRNA levels of these cases with "non-informative" 2+ score were lower than those recorded as high-level amplification, and further supported the notion that in these cases there was a relative reduction of protein expression despite HER-2 amplification. They also found that in almost half of those 2+ score cases, increased mRNA levels could be ascribed to HER-2 polysomy, verifying previous observations of immunohistologically detectable HER-2 polysomy [11] .…”
Section: Discussionsupporting
confidence: 67%
“…This problem has not been addressed specifically in many studies although it is common in practice. Kostopoulou et al [7] reviewed 13 studies in which the cases with IHC score 2+ were confirmed with FISH, and showed that the average percentage of the cases both with IHC score 2+ and HER-2 amplification was 21.2%, with a range of 8%-44.4%. A study in Taiwan had demonstrated that 53% of the IHC 2+ cases were HER-2 FISH positive [8] .…”
Section: Discussionmentioning
confidence: 96%
“…As discussed by Perreard et al [23] and Vinatzer et al [24] , the evaluation of Her2/neu mRNA expression did not show any statistically significant correlation with DNA amplification and protein expression. There was a clear overlap of expression levels of Her2/neu mRNA in the FISH and IHC subgroups, which could be explained on the heterogeneity of Her2/neu expression [25] . In spite of qRT-PCR representing an extremely sensitive and specific technique for determining transcript levels of Her2/neu [22] , cases with Her2/neu amplification and low Her2/neu mRNA levels were observed according to Gjerdrum et al [26] and Capizzi et al [27] .…”
Section: Discussionmentioning
confidence: 99%